PENGUATAN KONSEP SATUAN BERAT DAN VOLUME MELALUI MEDIA PEMBELAJARAN TANGGA SATUAN - Adelbertus Chun Chun; Ellisa Novitasari; Rafif Arkhab Kurniawan; Azamul Fadhly Noor Muhammad (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
This study aims to strengthen elementary school students’ understanding of weight and volume units through the use of unit ladder learning media. Difficulties in understanding unit relationships and unit conversions are common problems in elementary mathematics learning, as students often rely on memorization rather than conceptual understanding. This research employed a Systematic Literature Review (SLR) method to analyze and synthesize national research findings related to the use of concrete and visual learning media, particularly unit ladder media, in teaching weight and volume units. Data were collected from reputable national databases such as Google Scholar, SINTA, Garuda, and DOAJ, using keywords related to mathematics learning media and measurement units. The findings indicate that unit ladder media both manual and digital are effective in improving students’ conceptual understanding, reducing misconceptions, and enhancing accuracy and speed in unit conversion. The visual and hierarchical structure of the unit ladder helps students comprehend the relationships among units and facilitates the transition from concrete experiences to abstract mathematical reasoning. The study concludes that unit ladder learning media play a significant role in strengthening students’ understanding of weight and volume concepts and provide practical implications for elementary school teachers in designing effective and meaningful mathematics instruction. Keywords: Unit Ladder Media, Weight Units, Volume Units, Elementary Mathematics